Cultural adaptation of an internet-based intervention for the promotion of healthy lifestyle in Brazilian adolescents (Research, Society and Development, 2022)
Objectives: To describe the process of cultural adaptation of the American version of the StayingFit programme to the context of Brazilian adolescents and to test the usability of the adapted version. Methods: The adaptation process included translation of the material, synthesis of the translated versions, creation of the expert panel for reviewing the original and translated versions, and a pre-test of the adapted version. The usability of the programme was tested using the system usability scale (SUS). Results: Changes in the programme were made to make it compatible with the cultural standards, meanings, and values of Brazilian adolescents. Participants’ answers to usability tests reflected that they were satisfied with the format and content of the programme and demonstrated good understanding, ease of navigation, and approval of the VLE layout. Conclusion: The process of cultural adaptation of the StayingFit programme was successful and resulted in an easily understood prototype for adolescents.